Microbial and transcriptional differences elucidate atopic dermatitis heterogeneity across skin sites. Issue 4 (14th October 2020) - Ottman, Noora; Barrientos‐Somarribas, Mauricio; Fyhrquist, Nanna; Alexander, Helen; Wisgrill, Lukas; Olah, Peter; Tsoka, Sophia; Greco, Dario; Levi‐Schaffer, Francesca; Soumelis, Vassili; Schröder, Jens M.; Kere, Juha; et al.
Abstract: It is well established that different sites in healthy human skin are colonized by distinct microbial communities due to different physiological conditions. However, few studies have explored microbial heterogeneity between skin sites in diseased skin, such as atopic dermatitis (AD) lesions. To address this issue, we carried out deep analysis of the microbiome and transcriptome in the skin of a large cohort of AD patients and healthy volunteers, comparing two physiologically different sites: upper back and posterior thigh. Microbiome samples and biopsies were obtained from both lesional and nonlesional skin to identify changes related to the disease process. Transcriptome analysis revealed distinct disease‐related gene expression profiles depending on anatomical location, with keratinization dominating the transcriptomic signatures in posterior thigh, and lipid metabolism in the upper back. Moreover, we show that relative abundance of Staphylococcus aureus is associated with disease severity in the posterior thigh, but not in the upper back. Our results suggest that AD may select for similar microbes in different anatomical locations—an "AD‐like microbiome, " but distinct microbial dynamics can still be observed when comparing posterior thigh to upper back. This study highlights the importance of considering the variability across skin sites when studying the development of skin inflammation. Abstract : Distinct disease‐related gene expression profiles depend on anatomical location—keratinization is dominating in the posterior thigh and lipid metabolism in the upper back. Relative abundance of Staphylococcus aureus is associated with disease severity in the posterior thigh, but not in the upper back. The abundance of S aureus in posterior thigh is associated with keratinization and circadian rhythm regulating genes